INVESTIGATING STUDENTS' SCIENTIFIC LITERACY AND MOTIVATION USING INQUIRY BASED LEARNING SUPPORTED BY INSTAGRAM IN LEARNING LIGHT AND OPTIC TOPIC - Dhika Andraresti Lazuardi, - (2021)
Teaching and learning during pandemic unable the teacher and school to provide face to face class for the student. Therefore, we need to deliver the material to the students, as well as giving the students effective teaching and learning processes. The purpose of the study was to investigate the students' scientific literacy and students' Motivation toward Science Learning (SMTSL) using Inquiry-based Learning supported by Instagram. The method of this study is using a pre-experimental pretest and posttest design to measure the students' scientific literacy. The objective test will be used to measure the students' scientific literacy and questionnaire will be used in measuring Students Motivation towards Science Learning. The samples of this study consist of 17 students of 8th-grade students from one of the Junior High Schools in Bandung, Kuala Lumpur, and Yogyakarta. The n-gain result of the study shows that the students' scientific literacy is 0.127 which is described as low improvement. The n-gain result of the students' motivation towards science learning n-gain result is 75.71% which is described as good motivation with the highest n-gain in the science learning value domain with 82.82% which is described as very good motivation. The lowest n-gain result is in the self-efficacy and performance goal domain with 70.29% which is described as good motivation. Therefore, implementing inquiry-based learning supported by Instagram in the teaching and learning process able to improve the students' scientific literacy during distance learning as well as gain the students' motivation in learning science, especially in learning light and optic topic.